Triathlon anatomy - Klion, Mark 1962-; Jacobson, Troy (Human Kinetics, 2013)
This book shows you how to improve performance by increasing muscular strength and optimizing the efficiency of every movement. This title features 82 of the most effective multisport exercises with step-by-step descriptions and full colour anatomical illustrations highlighting the muscles in action